Quality Control To Reduce Defects in Ceramic Production Using Six Sigma Method and Root Cause Analysis: Pengendalian Kualitas Untuk Mengurangi Kecacatan Pada Produksi Keramik Menggunakan Metode Six Sigma dan Root Cause Analysis - Wahyudiyanto, Teddy; Wahyuni, Hana Catur (Universitas Muhammadiyah Sidoarjo, 2023)
PT. Kualimas Aditama is a company engaged in the manufacturing sector. This company has been a ceramics producer for 23 years. However, the problem faced in this company is that the level of product defects produced exceeds the company's tolerance limits. The company provides an acceptable tolerance for defective products of 3, but in fact the production of 60x60cm ceramics for 6 months in February 2023 had a product defect of 3.2% exceeding the tolerance limit which had a defect value of 1505 Pcs and a DPMO value of 8064.68899 with a sigma level of 3.9. In the define stage there were 4 product defects that occurred, namely ripe gupil of 2,668 pcs, raw gupil of 2,158 Pcs, ceramic scratched of 1,255 pcs and edge cracks of 586 Pcs. This study aims to determine damage to ceramics, determine the level of defects in ceramics and provide suggestions for improvements to reduce the number of defects. As an effort to reduce product defects that occur at PT.Kualimas Aditama, it is necessary to carry out quality control using the Six Sigma and RCA methods to improve production quality. From the results of the analysis, it is obtained that the triggering factors for product defects include human, machine, environmental factors. Highlights : Six Sigma Approach: Utilizing Six Sigma methodology for quality control allows for systematic problem-solving and process improvement. Root Cause Analysis (RCA): Identifying root causes of defects is crucial for implementing effective corrective measures. Human, Machine, Environmental Factors: Recognizing and addressing these factors are essential in reducing product defects and improving production quality. Keywords – Quality Control, Six Sigma, Root Cause Analysis